The Identification of The Students’ Conceptual Mastery of Fluid Statics: An Overview of Gender - Maria Claudia Sodakain; Sentot Kusairi; Nandang Mufti; Jane Koswojo (Jurnal Pendidikan Sains, 2023)
This study aimed to assess the conceptual mastery of fluid statics among students, employing a descriptive quantitative approach. The research involved 22 male and 13 female students from eleventh-grade MIPA at a private school in Surabaya, Indonesia. The primary research instrument comprised 11 multiple-choice and reasoning questions, covering concepts related to Pressure and Hydrostatic Pressure, Pascal’s Law, and Archimedes’ Principle. Results indicated a higher level of conceptual mastery among male students compared to their female counterparts. While both genders demonstrated relatively high conceptual mastery in Pressure and Hydrostatic Pressure, significant disparities were observed in their understanding of Pascal’s Law and Archimedes’ Principle. Notably, students encountered challenges in discussing Archimedes’ Principle, particularly in analyzing concepts related to sinking, floating, submersion, and buoyancy.DOI: 10.17977/jps.v11i32023p112